Self-blindness and self-knowledge - Parrott, M (Michigan Publishing, 2017)
Many philosophers hold constitutive theories of self-knowledge in the sense that they think either that a person’s psychological states depend upon her having true beliefs about them, or that a person’s believing that she is in a particular psychological state depends upon her actually being in that state. One way to support this type of view can be found in Shoemaker’s well-known argument that an absurd condition, which he calls “self-blindness”, would be possible if a subject’s psychological states and her higher-order beliefs about them were wholly distinct existences. A second reason to endorse a constitutive theory is the widespread conviction that first-person access is epistemically special. In this essay, I shall argue that even if self-blindness is impossible, the best explanation for this does not deny that a person’s psychological states are wholly distinct from her beliefs about them. I shall then attempt to account for the epistemic distinctiveness of first-person access on the basis of fundamental features of rational cognition. One advantage of this account over constitutive theories of self-knowledge is that it is better placed to explain our fallibility and ignorance.